Adaptive clothing for paraplegic individuals / Muhammad Ershad Kamari … [et al.] - Kamari, Muhammad Ershad; Saliang, Prinses; Ahmad, Hasma; Aris, Asliza (Research Innovation Business Unit, 2014)
Adaptive clothing for paraplegic individuals is actually a set of outfits specially designed for those who are paraplegic or in other words, a condition where their lower body is paralysed. Even though the main target is paraplegic person, it can also be worn by anyone who suffers from lower body disability. Besides fulfilling the needs in dressing, the design is hoped to provide some sense of style and fashion to the outfit. Some cumbersome aspects faced by the disabled are, some of the opening and closure are found to be difficult to be handled by a paraplegic person. Hooks and buttons are often found to be the problem. For this adaptive outfit, jacket and trousers was designed. The jacket is loose fitted so that it will provide comfort and be able to fit most of body type. The back of the jacket is shorter than the front so that it will not bother when sitting. In front are two spacious pockets for users to keep their personal stuff instead of carrying a bag with them since they need to utilize both their hands. The hoodie was added to style up the outfit so it will not look too boring. The hoodie is transformable in which it will lie flat on the back when it is not in use. As for the trousers, it has shorter crotch in the front and longer crotch in the back. The main problem about trousers is when you sit; the back waistline will drop thus exposing the back. Having longer crotch at the back will secure the position of the trousers when sitting. Darts at the knees will ensure the hemline of the trousers so it will not lift up when sitting. The opening is designed overlapped at the back in order to ease the burden when in toilet. In term of the production cost, it’s about RM200++ to produce. The cost is a bit high due to some experimentation during the making of it. The cost could go much lower than the initial production cost if produced in bulk. This outfit is hoped to be useful to the society and help paraplegic people in their daily life in particular. It is only a prototype and has the potential to be developed further in order to achieve the standards in dressing.